On the wurtzite to tetragonal phase transformation in ZnO nanowires - Wang, J.; Shen, Y.; Song, F.; Ke, F.; Liao, X.; Lu, Chunsheng (Institute of Physics Publishing Ltd., 2017)
There is a long standing contradiction on the tensile response of zinc oxide nanowires between theoretical prediction and experimental observations. Although it is proposed that there is a ductile behavior dominated by phase transformation, only an elastic deformation and brittle fracture was witnessed in experiments. Using molecular dynamics simulations, we clarified that, as the lateral dimension of zinc oxide nanowires increases to a critical value, an unambiguous ductile-to-brittle transition occurs. The critical value increases with decreasing the strain rate. Factors including planar defects and surface contamination induce brittle fracture prior to the initiation of phase transformation. These findings are consistent with previous atomistic standpoints and experimental results.